(untitled) (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The present study aimed to identify bacteria profile of cell phones used by different people from different profession of Bhaktapur and to access their antimicrobial resistance. Methods: Forty-nine mobile swab samples were collected from 7 different profession category (7 samples each from student, butcher, cook, panipuri vendor, health workers, and dairy employee). Samples were cultured and processed by standard Microbiological procedures. All the isolates were further subjected to antibiotic susceptibility testing using modified Kirby Bauer disc diffusion method as describe in CLSI guidelines. The rate of multiple drug resistant (MDR) bacteria was also determined. Results: Out of 49 sample, Bacillus spp (20.4%) was the most predominant isolate, followed by Staphylococcus aureus (10.6%) and Pseudomonas spp (10.6%). Higher variety of bacterial isolates was found in the cell phones swabs from butcher followed by cook, farmer and panipuri vendor group. The data from the questionnaire showed that handkerchief or tissue paper were mostly used by respondents to clean their mobile. All Gram-positive and Gram-negative isolates were resistance to Cefoxitin (100%) except Micrococcus spp and Neisseria spp. Gram positive (18.2%) and Gram-negative (36.9%) isolates were identified as MDR. All S. aureus and Coagulase negative staphylococci were methicillin resistant Conclusion: The Cell phones of people from different profession were found to possess many different bacterial pathogens including multi drug resistant strains which could be the possible pathogens for food borne infections and opportunistic infections.